Antracycline Induced Early Onset Chronic Cardiotoxicity in Cancer Patients - Idrees, Ibtisam; Ahmad, Riaz; Nadeem, Muhammad; Khan, Amjad; Gilani, Atifa; Khattak, Rahimullah (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the patients for early onset chronic cardiotoxicity who have been taking anthracyclines as part of their cancer treatment. Study Design: Comparative cross-sectional study. Place and Duration of Study: Oncology department, Combined Military Hospital, Rawalpindi Pakistan, from Dec 2020 to May 2021. Methodology: One hundred patients with solid or hematological malignancies taking anthracyclines for more than three months and less than a year were included in the study. They underwent 2 dimensional echocardiography by consultant cardiac physician to look for cardiotoxicity. Cardiotoxicity was defined as left ventricular ejection fraction less than 60%. Age, gender, duration of anthracyclines use and presence of comorbid illness were correlated with presence of early onset chronic cardiotoxicity in our study participants. Results: Out of 100 cancer patients using anthracyclines for more than three months and less than 12 months included in the study, 55(55%) were males while 45(45%) were females. Sixty-nine (69%) had ejection fraction more than 60% on echocardio-graphy while 31(31%) had <60%. Chi-square test revealed that presence of comorbidities (type 2 DM/ Hypertension) had statistically significant association with presence of cardiotoxicity in our study (p-value 0.002). Conclusion: Cardiotoxicity emerged as a significant adverse effect related to anthracycline use among patients suffering from various types of malignant conditions. Patients with preexisting medical conditions like diabetes or hypertension were more at risk of developing cardiotoxicity with these agents.